A PERSPECTIVE OF TECHNOLOGY ACCEPTANCE MODEL ON THE AGRICULTURE EXTENSION STAFFS USING CYBER EXTENSION - Padmaningrum, Dwiningtyas; Mani, La; Retnaningtyas, Triya Ayu; Sujatmiko, Tri; Subejo, Subejo; Widiyanti, Emi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Cyber extension web facilitates agriculture extension staffs to leverage this media communication system to strengthen their capability and capacity for improving extension services. Through the Technology Acceptance Model approach, this study examines the use of cyber extension and the affect of self-efficacy, perceived usefulness, perceived ease of use, subjective norms, and attitude toward usage on cyber extension usage by agriculture extension staffs in Central Java Province. This study was conducted from April to May 2023 using a quantitative approach. The population includes agriculture extension staffs within the scope of the Central Java Provincial Agriculture Office. Sampling was done using convenience sampling, with 377 agriculture extension staffs spreading across 28 districts and five cities. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The study showed that use of the cyber extension web can be categorized as low-level; meanwhile, self-efficacy, perceived ease of use, subjective norms, and attitudes towards positive use were relatively high. Cyber extension usage was directly affected by perceived ease of use, subjective norms, and attitude toward usage. As a recommendation, interventions are needed to improve and continue to update content variations. It is necessary to develop and optimize the use of cyber extension at the provincial and or district level.